Evidence of intertwined pair density and charge density wave orders in UTe 2 - Zhen Zhu; Yudi Huang; Julian May-Mann; Kaiming Liu; Zheyu Wu; Shanta R. Saha; Johnpierre Paglione; Alexander G. Eaton; Andrej Cabala; Michal Vališka; Eduardo Fradkin; Vidya Madhavan (Proceedings of the National Academy of Sciences, 2026)
The strongly correlated spin-triplet superconductor UTe 2 hosts an unusual magnetic-field-sensitive charge density wave (CDW) phase, positioning it as a compelling system for studying intertwined electronic orders. A central challenge is determining whether the observed charge modulations arise from a triplet pair density wave (PDW) order and, if so, how the anisotropic magnetic field response of triplet superconductivity is manifested in the CDW response. Here, using a scanning tunneling microscope equipped with a vector magnetic field, we systematically investigate the evolution and interrelation of distinct CDW orders. Complementing the previously identified incommensurate CDW peaks ( q i =1,2,3 ), we resolve an additional set of nondispersive modulations ( p i =1,2,3 and h 1,2 ) with distinct temperature and magnetic field dependencies. The p i CDW peaks vanish near T c , while the q i peaks survive well above T c but are progressively suppressed by magnetic field in an anisotropic manner. The critical fields of the q i peaks mirror the directional hierarchy of H c2 , which suggests a PDW is present above the bulk T c . This is consistent with a Landau free-energy picture where PDWs with wavevectors p i form above the bulk T c , leading to composite CDW orders with wavevector q i . Below T c , the coupling of PDWs and uniform superconductivity leads to the p i CDWs. Together, these findings establish UTe 2 as a rare platform where both the parent PDW and descendant orders are directly resolved, enabling access to both the fundamental and emergent manifestations of PDW physics.